1-3 John - O'Donnell, Douglas Sean, 1972- (Phillipsburg, NJ : P & R Pub., 2015)
How can we know that we possess eternal life? The apostle John answered that question in the three epistles that bear his name. He wrote that we must firstly believe that Jesus is the Son of God and that Christ came in the flesh. Secondly, we are to obey God's commandments. Thirdly, we must love others. In this illuminating and engaging commentary on John's letters, pastor-scholar Douglas Sean O'Donnell illustrates and applies these three essential tests that judge whether we possess eternal life or not. Grow in your knowledge of Christ, our Savior. Learn how to live in the light. Grab hold of the gospel-transformed life! -- Amazon.com.
Apostolic fellowship (1 John 1:1-4) -- Live in the light (1 John 1:5-10) -- Advocacy and example (1 John 2:1-6) -- Why love matters (1 John 2:7-11) -- Knowing Christ and overcoming the devil (1 John 2:12-14) -- What not to love (1 John 2:15-17) -- Antichrist is coming (1 John 2:18-27) -- The appearance is everything (1 John 2:28-3:10) -- What we know (1 John 3:11-24) -- Who's got your ear? (1 John 4:1-6) -- The two loves (1 John 4:7-21) -- The nature and knowledge of the faith (1 John 5:1-12) -- Festival of faith (1 John 5:13-21) -- In truth and love (2 John) -- Seven important lessons from 219 inspired words (3 John).
Includes bibliographical references (pages 201-203) and index.
Keywords: Bible. -- Commentaries